(untitled) (قضايا سياسية, 2025)
This research focuses on studying the reality of political participation and community dialogue in Anbar Governorate, and seeks to analyze the reasons that led to the decline of these two important aspects in the post-conflict environment, while highlighting the importance of promoting popular participation and dialogue in achieving political and social stability. The research aims to provide practical solutions and proposals that contribute to activating the role of citizens and building bridges of trust between various segments of society and state institutions.